KOMUNIKASI PEMBANGUNAN PROGRAM I-YES MENGAJAR DALAM MENINGKATKAN KUALITAS PENDIDIKAN MELALUI AGENDA SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI PROVINSI RIAU - Risman, M. Hafiz; Sari, Genny Gustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted with a qualitative approach. The number of informants was 6 people consisting the member of I-YES Indonesia and a headmaster as supporting informant. The technique of collecting data is by conducting semi-structural interviews and documentation. All data were then analyzed qualitatively and were triangulated to describe the development communication of I-YES Mengajar. The results showed that the contribution of I-YES Mengajar to improve the quality of education through SDGs agenda is still not dominant and is vague to which target and indicator to achieve. This research found that due to subjectivity of innovation, this program can be categorized as an innovation for its adopter. Secondly, the communication channel used are quite diverse, starting from interpersonal channels, groups, to mass media. The third is time, in which every implemented program has been confirmed with positive results, as well as a consistent adoption rate during implementation. Finally, the social system, because of the location of the implementation is only one province makes the social structure similar to one another which also in line with social norm resulted to no special rules that need be considered by this program. Keywords: Development Communication; Diffusion of Innovation; Sustainable Development Goals; Quality Education; Non-Governmental Organisation